2005
DOI: 10.1111/j.1460-9592.2005.01660.x
|View full text |Cite
|
Sign up to set email alerts
|

Does dexmedetomidine prevent emergence delirium in children after sevoflurane‐based general anesthesia?

Abstract: The perioperative infusion of 0.2 microg.kg(-1).h(-1) dexmedetomidine decreases the incidence and frequency of ED in children after sevoflurane-based GA without prolonging the time to extubate or discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
178
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(191 citation statements)
references
References 31 publications
12
178
0
1
Order By: Relevance
“…9 Several prospective clinical trials in children have shown that dexmedetomidine significantly reduces the incidence of EA prior to recovery from sevoflurane anesthesia. [10][11][12][13] Ketamine is an N-Methyl-D-aspartate (NMDA) receptor antagonist used clinically as an anesthetic, sedative, and analgesic in pediatric patients undergoing strabismus surgery. It has been reported that ketamine can lower the incidence of postoperative EA, POV, and pain following strabismus surgery when compared with propofol.…”
Section: Résumémentioning
confidence: 99%
“…9 Several prospective clinical trials in children have shown that dexmedetomidine significantly reduces the incidence of EA prior to recovery from sevoflurane anesthesia. [10][11][12][13] Ketamine is an N-Methyl-D-aspartate (NMDA) receptor antagonist used clinically as an anesthetic, sedative, and analgesic in pediatric patients undergoing strabismus surgery. It has been reported that ketamine can lower the incidence of postoperative EA, POV, and pain following strabismus surgery when compared with propofol.…”
Section: Résumémentioning
confidence: 99%
“…A P < 0.0125 was considered statistically significant, accounting for a Bonferroni correction in comparison of four groups and a P < 0.05 was considered statistically significant in comparison of experimental groups and control groups. 5,17 The change in the end-tidal concentration of sevoflurane, propofol and fentanyl were analysed by repeated measures ANOVA, and post-hoc testing was performed using the turkey and t-test. A P < 0.05 was considered statistically significant between two groups.…”
Section: Discussionmentioning
confidence: 99%
“…The tube was fixed and then connected to ventilator. Anaesthesia was maintained by N2O:O2 (2:1) and sevoflurane which was titrated to 1 MAC (minimal alveolar concentration) 5,6 14 Mechanical ventilation was maintained with 8 ml/kg tidal volume and ventilation frequency was adjusted to maintain ETCO2 between 30-40 mmHg.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Despite the lack of FDA labeling in pediatrics, dexmedetomidine has become a widespread therapeutic option for children in the PICU and operating room settings. 12 Multiple trials have examined dexmedetomidine to sedate mechanically ventilated children, [13][14][15][16] to prevent emergence delirium after general anesthesia, [17][18][19][20] and for both invasive 21,22 and noninvasive [8][9][10][11] procedural sedation.…”
Section: Discussionmentioning
confidence: 99%